Réponses

2014-05-27T18:25:42+02:00
F(x) = -2x+5
f(2) = -2*2+5
f(2) = -4+5
f(2) = 1

f(x) = -2x+5 = 0
-2x = -5
x = -5/-2
x = 5/2= 2,5

système:
9x+7y = 2
3x+4y = -1

on multiplie la 2ième par -3 : -9x-12y = 3
on additionne les 2 :
9x+7y -9x-12y = 2+3
-5y = 5
y = -5/5
y = -1
 
3x-4 = -1
3x = 4-1
3x = 3
x = 1
  • Utilisateur Brainly
2014-05-27T18:37:14+02:00
                               f(x)=-2x+5

1) Déterminer l'image de 2 :
f(2)=-2*2+5 \\ =-4+5 \\ =1
f(2)=1

2) Déterminer l'antécédent de 0 :
-2x+5=0 \\ 5=2x \\ 5/2=x \\ 2.5=x

3) Calculer :
9x+7y = 2 \\ 3x+4y = -1


-9x-12y = 3 \\ 9x+7y-9x-12y=3+2 \\ 9x-9x+7y-12y=5 \\ -5y=5 \\ -y=1 \\ y=-1
3x-4 = -1 \\ 3x = -1+4 \\ 3x = 3 \\ x = 3/3 \\ x=1

S={-1 ; 1}